GEREJA MASEHI INJILI DIBOLAANG MONGONDOW (GMIBM) PUSAT KOTAMOBAGU (1923-2014) - MAMENTU, DIANA NATALIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT ÂThe Â topic ofÂ the research is â€œGereja Masehi Injili di Bolaang Mongondowâ€ (GMIBM) Pusat Kotamobagu 1923 â€“ 2014. Focus of the research on 3 (three) important points : The beginning of the Gospel in Bolaang Mongondow.How to process of the Christian Evangelical Church in Bolaang Mongondow (GMIBM) Kotamobagu Center was born.The growing of the Christian Evangelical Church in Bolaang Mongondow (GMIBM) Kotamobagu Center since 1923 â€“ 2014. The Methods to used in this research were : Heuristic, Critic and Analyzing, Interpretation, Historiography. Source of the research is show that Gospel comes in Bolaang Mongondow to brought by Europen (Spain, Portugal, Netherlands). Church of Kotamobagu center was born since 1910 â€“ 2014 and then consecrated on February 23 th 1923.